The Effect on Mathematical Learning Outcome by Modelling of Mathematic Learning and Cognitive Style of Junior High Students - ., Nurhamiyah; ., Mustaji; ., Suryaman (International Journal of Educational Technology and Learning, 2019)
The objectives of this study are (1) to examine a difference between the learning outcome of junior high school students who participate in Realistic Mathematic Learning (RML) and expository, (2) to examine a difference between learning outcome of students who have cognitive style of Field Dependent (FD) and Field Independent (FI), and (3) to examine an interaction between the students who participate in RML and cognitive style on mathematical learning outcome. The study is conducted at two religion-based state junior high school in Surabaya, Indonesia. Data collecting instrument of cognitive style uses Withkin’s Group Embedded Figure Test (GEFT). The test is used to measure mathematical learning outcome. The results of study show a significance value on PMR of 0.001 < 0.05 with F-count = 10.715. For the significance value on cognitive style, it is obtained a significance value of 0.000 < 0.05 with F-count = 180.928. While the significance value on RML and cognitive style, it is obtained 0.013 < 0.05 with F-count = 6.311. So, it can be concluded that (1) there is the difference between learning outcome of students who participate in PMR model and expository learning, (2) there is the difference between learning outcome of the students who have a cognitive style of FD and FI, and (3) there is the interaction between RML model and cognitive style on students’ learning outcome.